RELATIONSHIPS OF ADOLESCENT LEVEL ABOUT ABORTION WITH ADOLESCENT ATTITUDES TO ABORTION IN PELITA VOCATIONAL HIGH SCHOOL BOGOR : HUBUNGAN TINGKAT PENGETAHUAN REMAJA TENTANG ABORSI DENGAN SIKAP REMAJA TERHADAP ABORSI DI SMK KESEHATAN PELITAKABUPATEN BOGOR - Nining Fitrianingsih (Wijaya Husada, 2018)
dolescents in Indonesia experience pregnancy and birth before marriage reached20.9%, this figure is a fairly high and alarming. Based onthepreliminary studies on 10 female students, it was known that all female students knew about abortion through information media and 4 female students thought that abortion was dangerous but 6 other female students consideredthat abortion are normal, and the results of information obtained from the conselourteacher (BK) that there was once one student who was pregnant out of wedlock and had an abortion so that the student was expelled from school. The aims of this research areto determine the relationship of the level of knowledge of adolescents about abortion with adolescent attitudes towards abortion in students / class XI at Vocational Health Pelita Bogor in 2017. This research uses a quantitative study with a correlational design using a cross sectional approach. The populationused total sampling technique, there was 95 students of grade XI. The 95 respondents, 51 (53.7%) students had good knowledge about abortion, and 61 (64.2) positive attitudes towards abortion. Based on the statistical test results obtained p value = 0.00 which means p Value <0.05 so HO is rejected and HA is accepted, which means there is a relationship between the level of knowledge of adolescents about abortion with adolescent attitudes towards abortion in class XI in Vocational School Health Pelita District Bogor. It is expected to provide good knowledge about abortion so that it can increase knowledge about abortion and attitudes towards abortion and not fall prey to free sex which results in abortion.